Implementation of Inclusive Education at SDN Ciracas 15 Pagi - Fikri, Hafizh Irsyadul; Alkhoiri, Muhammad Faiz; Zulfadewina, Zulfadewina (Lembaga Riset Mutiara Akbar, 2025)
This research aims to determine the effectiveness of the inclusion program in improving the academic and social achievement of students with special needs (SBK) at SDN Ciracas 15 Pagi. The inclusion program is an effort to provide equal access to education for SBK by providing a learning environment that supports their individual needs. The research method used is descriptive qualitative, with data collection through observation, interviews and documentation. The research results show that the inclusion program at SDN Ciracas 15 Pagi has had a positive impact on SBK's academic and social development. From an academic perspective, there is an increase in SBK's reading, writing and arithmetic abilities through the application of adaptive learning methods. Meanwhile, from a social aspect, interactions between SBK and regular students show significant development, with SBK's increased self-confidence and communication skills in the school environment. The success of this program is supported by the role of special mentoring teachers (GPK), curriculum adjustments, and support for inclusive learning facilities.